The Photo-stimulated Peltier Effect in Rectangular Quantum Wires under the Influence of Confined Phonons - Anh, Nguyen Thi Nguyet; Dien, Tang Thi; Ba, Cao Thi Vi; Ngoc, Hoang Van (VNU Journal of Science: Mathematics - Physics, 2022)
Based on the kinetic equation method, the quantum Peltier effect has been theoretically studied under the influence of confined optical phonons in a rectangular quantum wire (RQW) of infinite high potential when placed in perpendicular electric and magnetic fields. There were complicated dependences of the analytical expression of the Peltier coefficient (PC) on quantities such as the size of the wires amplitude of the laser radiation, the cyclotron frequency of electrons and temperature of the system. Moreover, the presence of a strong electromagnetic wave (EMW) is also taken into account to determine the influence of confined phonons on the aforementioned effects. We have defined the analytical expressions for the kinetic tensors and PC. In detailed consideration, the quantum numbers m 1 , m 2 were changed in order to characterize the influence of confined optical phonons. The results of setting the m 1, m 2 to zero showed that this case can be seen asthe unconfined optical phonon. This means that the confinement of the phonon affects the Peltier effect quantitatively and qualitatively. The theoretical results have been numerically evaluated and discussed for the GaAs/GaAsAl quantum wires. The change of the confinement and non-confinement phonons upon the change of the magnetic field shows that the height of the resonance peaks in the confinement case is about 4 times larger than the non-confinement case. The position of the resonance peak in the two cases are also shifted. The size of the wire in the case of the confinement phonon is more pronounced and stable than in the non-confinement case. The new results obtained can provide for completing the theory of the Peltier effect in low - dimensional semiconductor systems.